Mangrove Project: Pendidikan Masyarakat Berbasis Edupreneurship - Fuad Abdullah (Populer: Jurnal Penelitian Mahasiswa, 2024)
In this research, the concept of edupreneurship is used as an approach in designing the process of applying creativity in providing education to the public about opportunities to increase financial coffers. The potential for good cooperation between pkk mothers who meet every week and the abundant natural potential can increase income and add value. One of the abundant potentials is the mangrove plant whose leaves and fruit can be used. This research aims to (1) map the environmental and economic potential of the Tapak Village community with an edupreneurship perspective (2) Increase community creativity, especially coastal communities which have abundant mangroves (3) Create jobs for the community to increase financial coffers. The research method used in this research was carried out by a project in Tapak Village. Data obtained through interviews and documentation. with research subjects namely the community of pkk mothers in Tapak Village, Tugu District, Semarang City. The research results show that the potential of the Tapak Village community has abundant resources in the form of mangrove plants, considering that the community is enthusiastic and united. Abundant resources in the form of mangrove plants can be used as processed food which has sales value in the field of health snacks.